2005
DOI: 10.1051/rnd:2005008
|View full text |Cite
|
Sign up to set email alerts
|

An early stimulation of solid feed intake slightly influences the morphological gut maturation in the rabbit

Abstract: -The impact of dietary factors on the gut morphological maturation is poorly documented in rabbits. The weights of the digestive segments as well as the morphology of villi and crypts along the small intestine were analysed weekly from day 14 till day 49, in two rabbit groups weaned at either 21 (W21 group, n = 12 litters) or 35 days (W35 group, n = 12 litters) of age. From 21 till 35 days, the W21 group ate 57% more solid feed than the W35 group (P < 0.01), and presented slighter body weights from day 28 till… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
32
2
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 31 publications
(39 reference statements)
9
32
2
6
Order By: Relevance
“…There was a reversed proportion between the weight of the stomach and the caecum, that is, before weaning (day 14) the stomach accounted for 38% of the GI tract, whereas its proportion decreased to between 29% and 32% by the time around weaning; however, the relative weight of the caecum increased from 12% (before weaning) to between 29% and 32% at 42 days of age. This is also in agreement with previous findings of Lebas and Laplace (1972) and Gallois et al (2005), who discussed the role of the different digestive organs in rabbits, assigning increasing importance to the large intestine with age and with increasing solid feed intake. Changes in the amount of the gastric content occurred with weaning.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There was a reversed proportion between the weight of the stomach and the caecum, that is, before weaning (day 14) the stomach accounted for 38% of the GI tract, whereas its proportion decreased to between 29% and 32% by the time around weaning; however, the relative weight of the caecum increased from 12% (before weaning) to between 29% and 32% at 42 days of age. This is also in agreement with previous findings of Lebas and Laplace (1972) and Gallois et al (2005), who discussed the role of the different digestive organs in rabbits, assigning increasing importance to the large intestine with age and with increasing solid feed intake. Changes in the amount of the gastric content occurred with weaning.…”
Section: Discussionsupporting
confidence: 93%
“…The data of Feugier et al (2006), who investigated the fibre and protein requirement of early weaned rabbits, suggested that the detrimental effect of early weaning was not compensated for by a diet better meeting the young rabbits' nutrient requirements. Few experiments have been conducted in which only the impact of age at weaning was studied (Gallois et al, 2005 and2008).…”
Section: Introductionmentioning
confidence: 99%
“…The increased activity of APN in early-weaned rabbits may result more from differences in the quality of peptides ingested than from their quantity. Indeed, amounts of ingested proteins by suckling rabbits with free access to pelleted feed were higher from 21 till 28 days of age, then similar between 28 and 35 days as compared with early-weaned rabbits (Gallois et al, 2005). This observation reinforces the assertion that APN would be more implicated in the digestion of peptides of vegetal origin.…”
Section: Discussionsupporting
confidence: 75%
“…Conversely, Gutié rrez et al (2002) observed lower maltase and sucrase activities in weaned rabbits, compared with suckling 35-day-old rabbits, probably as a consequence of the negative impact of an early weaning on mucosa morphology. But, we found any detrimental effect of an early weaning on mucosa morphology (Gallois et al, 2005). The increased activity of APN in early-weaned rabbits may result more from differences in the quality of peptides ingested than from their quantity.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation